2002
DOI: 10.1073/pnas.252415599
|View full text |Cite
|
Sign up to set email alerts
|

Host–pathogen interactions: Host resistance factor Nramp1 up-regulates the expression of Salmonella pathogenicity island-2 virulence genes

Abstract: Nramp1 (Natural resistance-associated macrophage protein-1; also known as Slc11a1) is a host resistance gene that provides protection against several intracellular pathogens, including Salmonella enterica serovar Typhimurium. Little is known about the dynamic interplay that occurs between mammalian host resistance determinants such as Nramp1 and pathogens during infection. To explore these interactions, we examined the effect of Nramp1 on expression of Salmonella typhimurium (STM) virulence factors. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 42 publications
6
83
1
Order By: Relevance
“…The expression of SPI-2 TTSS structural components and the associated secreted effectors is induced specifically inside host cells (Cirillo et al, 1998;Shea et al, 1996;Valdivia & Falkow, 1997), as well as under in vitro conditions that mimic the intracellular environment of the SCV, which include low osmolarity (Garmendia et al, 2003;Lee et al, 2000), calcium limitation (Garmendia et al, 2003), phosphate limitation (Deiwick et al, 1999) and iron limitation (Zaharik et al, 2002). The induction of SPI-2 genes in response to these stimuli is dependent on SsrA (also referred to as SpiR)/SsrB, a two-component regulatory system encoded within the SPI-2 region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of SPI-2 TTSS structural components and the associated secreted effectors is induced specifically inside host cells (Cirillo et al, 1998;Shea et al, 1996;Valdivia & Falkow, 1997), as well as under in vitro conditions that mimic the intracellular environment of the SCV, which include low osmolarity (Garmendia et al, 2003;Lee et al, 2000), calcium limitation (Garmendia et al, 2003), phosphate limitation (Deiwick et al, 1999) and iron limitation (Zaharik et al, 2002). The induction of SPI-2 genes in response to these stimuli is dependent on SsrA (also referred to as SpiR)/SsrB, a two-component regulatory system encoded within the SPI-2 region.…”
Section: Introductionmentioning
confidence: 99%
“…In Salmonella-infected epithelial cells, the SCV forms long filamentous structures referred to as Salmonellainduced filaments (Sifs), which are elongated tubules that appear to extend from the SCV membrane along the host cell microtubules (Guignot et al, 2004). (Zaharik et al, 2002). The induction of SPI-2 genes in response to these stimuli is dependent on SsrA (also referred to as SpiR)/SsrB, a two-component regulatory system encoded within the SPI-2 region.…”
mentioning
confidence: 99%
“…Found in many Gram-negative pathogenic bacteria, T3S is a needle-like structure that physically connects the cytoplasms of bacterial and host cells, permitting direct translocation of bacterial effector proteins into the cytosol of host cells to alter the function of host cells in favor of disease progression (6 -9). Nramp1 activity competes with the ability of STM to control the biogenesis of SCV, probably via up-regulation of some SPI-2-related genes, and increases the traffic of lysosomal hydrolases to the SCV to facilitate the killing of STM (10,11).…”
mentioning
confidence: 99%
“…This proposition is supported by recent experiments with Salmonella carrying a number of transcriptional LacZ fusions that were used to infect Nramp1-positive and -negative mice in vivo, and corresponding macrophages ex vivo. These studies showed that intracellular Salmonella respond to the presence of Nramp1 by induction of a number of ''virulence'' genes that map within Salmonella pathogenicity island 2 (SPI2), including ssrA and sseJ (45). The Nramp1 effect on SPI2 gene induction in vivo can also be reproduced in vitro in cell-free conditions after addition of iron chelators (such as dipyridyl) to Salmonella culture medium (45).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that intracellular Salmonella respond to the presence of Nramp1 by induction of a number of ''virulence'' genes that map within Salmonella pathogenicity island 2 (SPI2), including ssrA and sseJ (45). The Nramp1 effect on SPI2 gene induction in vivo can also be reproduced in vitro in cell-free conditions after addition of iron chelators (such as dipyridyl) to Salmonella culture medium (45). Similarly, we have noted an effect of Nramp1 on the level of transcriptional induction of the mycobacterial gene MbtB (J. R. Forbes and P.G., unpublished data) that participates in the synthesis of iron siderophores (mycobactins) and that is absolutely required for intracellular survival of Mycobacterium tuberculosis (46).…”
Section: Discussionmentioning
confidence: 99%